Genotoxicity Biomarkers Study in Agricultural Workers Exposed to Pesticides: a Systematic Review - Edisson Vladimir Maldonado Mariño; Darío Orlando Siza Saquinga; Diego Eduardo Guato Canchinia; Alexander Javier Ramos Velastegui (Medisur)
Exposure to pesticides by farmers leads to serious health problems. Genotoxicity biomarkers are an effective tool to assess the impact of pesticides on genetic material. A literature review was conducted to gain insight into genotoxicity biomarkers in South American agricultural workers exposed to pesticides. It was found that exposure to these chemicals can have adverse health effects, such as neurological, respiratory, dermatological, endocrine disorders and cancer. Its effects depend on the type, dose, duration of exposure, work and environmental conditions. Among the most commonly used biomarkers to determine the impact are: the comet assay and the cytokinesis blocking micronucleus assay, in addition, some specific ones at the genetic level were used, such as the polymerase chain reaction. The importance of developing policies and programs that promote the prevention of exposure to pesticides in order to protect the health of agricultural workers and the general population was highlighted.